The Role, Development and Opportunities of Spice Commodities for International Relations Between Indonesia and Other Countries in The International Market - Saputro, Wahyu Adhi; Anggrasari, Herdiana (JASSP, 2021)
Indonesia as a spice producer has the opportunity to become a world spice exporter that can contribute to the Indonesian economy. On the other hand, Indonesia has challenges to be able to improve the performance of Indonesian spices commodities. In this research, an overview of the condition of Indonesian spices will be seen so that the development and opportunities of Indonesian spices can be identified. Therefore the objectives of this study are (1) to determine the development of the area, production and productivity of Indonesian spices, (2) to determine the development and performance of international trade in Indonesian spices, (3) the demand for world and Indonesian spices. in the international market, and (4) the development of world and Indonesian spices prices in the international market. This research uses the basic analytical descriptive method, which is a research method that focuses on solving actual problems in the present. The results showed that in general the acreage and production of spices commodities tended to increase from year to year, but the productivity of pepper, nutmeg and vanilla decreased. When viewed from the balance of the Indonesian spices trade in each period it fluctuates but tends to increase. Meanwhile, the demand for spices in the international and Indonesian markets fluctuates every year but tends to increase and the development of international and domestic spice commodity prices has fluctuated each period.